2015
DOI: 10.1038/onc.2015.442
|View full text |Cite
|
Sign up to set email alerts
|

Inactivating mutations in GNA13 and RHOA in Burkitt’s lymphoma and diffuse large B-cell lymphoma: a tumor suppressor function for the Gα13/RhoA axis in B cells

Abstract: G-proteins and their cognate G-protein coupled receptors (GPCRs) function as critical signal transduction molecules that regulate cell survival, proliferation, motility and differentiation. The aberrant expression and/or function of these molecules have been linked to the growth, progression and metastasis of various cancers. As such, the analysis of mutations in the genes encoding GPCRs, G-proteins and their downstream targets provides important clues regarding how these signaling cascades contribute to malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
60
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 47 publications
6
60
1
Order By: Relevance
“…Another study also showed inactivating mutations in components of the GPCR signaling pathway (i.e. GNA13 and RHOA) genes, suggesting that this pathway may be a target of therapy for GNA13 or RHOA-mutated BL cases (O'Hayre et al, 2016).…”
Section: Burkitt Lymphomamentioning
confidence: 98%
“…Another study also showed inactivating mutations in components of the GPCR signaling pathway (i.e. GNA13 and RHOA) genes, suggesting that this pathway may be a target of therapy for GNA13 or RHOA-mutated BL cases (O'Hayre et al, 2016).…”
Section: Burkitt Lymphomamentioning
confidence: 98%
“…Mutations in GNA13 have been characterized in both liquid and solid tumors and are present at high frequency in bladder carcinoma. In addition, recent genome-wide sequencing efforts have unveiled the presence of frequent mutations in GNA13 in lymphomas, specifically Burkitt's lymphoma and diffuse large B-cell lymphoma (DLBCL) (71)(72)(73). These mutations in GNA13 as well as in RhoA, a downstream target of G␣ 13 , have been shown to be inhibitory in nature, suggesting a tumorsuppressive role for G␣ 13 and RhoA in Burkitt's lymphoma and DLBCL (71).…”
Section: Significantly Mutated G Proteins In Cancermentioning
confidence: 99%
“…In the report about AITL and BL, G17V and R5Q mutations reduce the guanosine triphosphate (GTP)-binding form of RHOA, and the downstream effector activities like serum response factor transcription and the stress fiber formation significantly decreased. 2,3,8 In addition, it has been shown that the loading of GTP does not occur by G17V mutation. In the case of Y42C mutations in gastric cancer, it has also been shown that the adenosine triphosphate-bound active form has decreased, whereas another report showed selective loss of binding of RHOA to protein kinase N (PKN) effector protein.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The disease categories, mutations, and biochemical properties linked to increased and decreased RHOA activity are indicated by red and blue color, respectively. Image of 1A2B 10 created with PyMOL (Schrödinger, LLC).…”
mentioning
confidence: 99%